Unreliable Narration and Point of View in the Film Birdman (2014) - Núñez-Alberca, Alejandro (2025)
The point of view, extensively studied by formalist, semiotic, and narratological theories, represents a mediation of considerable importance between the viewer and the filmic discourse unfolding before it, especially when attributing which events in the narrative are true and which are imagined within the diegesis. Therefore, this paper aims to identify the variations in point of view present in the film Birdman (2014) and describe the audiovisual language strategies on which these changes are based. The study adopts a qualitative approach, and the chosen methodology was textual analysis. After identifying the main aesthetic elements of the film, it is concluded that Birdman constitutes a case of unstable narration, as it not only tells its story from the perspective of a mentally disturbed character but also creates complexity in the criteria necessary for the viewer to discern between what is true and what is simulated within the diegesis through a meticulous control of cinematic forms of expression.